An experimental investigation of the effects of dynamic motions on a delta wing - Yeoh, Chee Wai. (2012)
The final year project involves the investigation on the vortex breakdown phenomenon associated with dynamic pitching and dynamic rolling delta wing. Experimental investigation was performed on a 70o sweep delta wing with aspect ratio 1.46 at a Reynolds number of 15750in a water tunnel of Nanyang Technological University. The vortex breakdown location of delta wing under steady state and dynamic motion was visualized using dye injection.